2018
DOI: 10.1002/ejoc.201800431
|View full text |Cite
|
Sign up to set email alerts
|

KOtBu‐Mediated Aza‐Michael Addition of Aromatic Amines or N‐Phenylurea to 3‐Nitro‐2‐phenyl‐2H‐chromenes and Sequential Aerobic Dehydrogenation

Abstract: A highly efficient KOtBu‐mediated aza‐Michael addition of aromatic amines and/or N‐phenylurea derivatives to 3‐nitro‐2‐phenyl‐2H‐chromenes and sequential aerobic dehydrogenation is reported. This method provides a novel protocol for C–N bond formation in 3‐nitro‐2‐phenyl‐2H‐chromenes under cost‐effective and operationally convenient conditions. A wide range of 4‐(phenylamino)‐3‐nitro‐2‐phenyl‐2H‐chromenes have been synthesized in good‐to‐high yields (68–86 %) at 35–40 °C within 5–10 minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 51 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Nucleophilic intermediates can be formed via deprotonation of aniline derivatives by a base and stabilization of the anion through various possible resonance structures 46,47 . This initial deprotonation represents an equilibrium reaction, which shifts depending on the concentration of the base in relation to the aniline reagent.…”
Section: Resultsmentioning
confidence: 99%
“…Nucleophilic intermediates can be formed via deprotonation of aniline derivatives by a base and stabilization of the anion through various possible resonance structures 46,47 . This initial deprotonation represents an equilibrium reaction, which shifts depending on the concentration of the base in relation to the aniline reagent.…”
Section: Resultsmentioning
confidence: 99%
“…So, keeping this concept in mind, a lewis base DABCO catalyzed one pot and efficient formation of various substituted (dihydro)thieno simple procedure, high substrate scope, readily available starting materials, and satisfactory yield are the general advantages of this reaction (Scheme 7). [52] Keeping the usefulness of heterocyclic fused chromanes and hybrid of chromane scaffolds in mind, Sun and his coworkers demonstrated Michael addition followed by an annulation reaction of two molars of pivaloylacetonitrile 26 and benzoyl acetonitrile 27 to 2-aryl-3-nitro-2H-chromenes 25 using NEt 3 as a base. The domino reaction provided the multifunctionalized imino-substituted furo[2,3-c]chromenes 28, ethoxy/methoxy-substituted chromeno [3,4-b]pyridines 29 when refluxing in ethanol/methanol and furo[2,3-c]chromene derivatives 30 with good yields respectively.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Short reaction time, simple procedure, high substrate scope, readily available starting materials, and satisfactory yield are the general advantages of this reaction (Scheme 7). [52] …”
Section: Michael/hetero‐michael Addition Reactions Of 3‐nitro‐2h‐chro...mentioning
confidence: 99%
“…Bor‐Cherng Hong et al reported enantioselective synthesis of tetrahydro‐6 H ‐benzo[c]chromenes via Domino Michael–Aldol condensation using organo‐catalyst multicomponent reaction [11]. Most recently, Naseem Ahmed et al reported KO t Bu ‐mediated functionalization of 3‐nitro‐2‐phenyl‐2 H ‐chromene via oxidative aza Michael addition using aniline as Michael donor [12]. Sabita Nayak et al in 2019 simultaneously developed two microwave assisted multicomponent strategies for the synthesis of highly functionalized chromene derivatives via 1, 3 dipolar cycloaddition reaction [13].…”
Section: Introductionmentioning
confidence: 99%